Incarcerated femoral hernia with ovarian contents - Rondon-Tapia, Martha (2021)
Femoral hernias account for less than 10% of inguinal hernias; they occur especially in adult women and have a higher rate of complications associated with incarceration compared with other abdominal hernias. The most frequent contents inside the hernia sac are intestinal loops, preperitoneal fat and omentum. Other abdominal structures, such as appendix, bladder, Meckel's diverticulum, ectopic testis and stomach are extremely rare. The uterus, ovary, and fallopian tubes are rarely present in an inguinal hernia. Incarcerated femoral hernia with ovary as content is an extremely rare condition in adult females. Most cases occur in girls and are often associated with congenital defects of the genitalia. Preoperative diagnosis to establish the contents of the hernia can be difficult, but conventional ultrasonography can be helpful in identifying the characteristics of the contents. The traditional treatment is open repair. However, laparoscopic surgery makes it possible to confirm the diagnosis and evaluate the possibility of ischemic changes in the contents of the hernia sac. A case of incarcerated femoral hernia with ovarian content is presented.